Active and passive participial adjectives in English: Errors commonly made by students at Lang Son technical & economic secondary school and some proposed solutions - Hoang, Thi Hai (ĐHNN, 2017)
This research aimed to discover common errors made by students in using English Participial Adjectives. The participants of the study were 100 the first-year students (aged 18-30). They are from classes K29A1, K29A5, Business Accounting of Lang Son Technic (...)